Causas que impedem a inclusão de pessoas com deficiência no mercado de trabalho no município em Parintins-AM - Lopes, Rosiele Bentes (Brasil, 2024)
This research aimed to identify the causes that prevent the full inclusion of people with disabilities in the job market in Parintins – AM from the perspective of the low number of PwD employees within companies, considering the application of the Quota Law in the focus companies, as well as the perspective of people with disabilities regarding the work environment. We sought to analyze the causes that impede the inclusion of people with disabilities in the local job market. The focus was on five companies that fell within the parameters of Law 8,213/91. The study had theoretical support from studies that address concepts about social inclusion discussed by authors such as Silma Perez Cruvinel (2023) and Juliana Marinho Cavalcante Paiva; Pedro F. Bendassolli (2017), as well as studies on the labor market and the basis for the Quota Law with data from the legislation, presented on the Planalto website. The research was based on the observation that some companies in Parintins comply with legal obligations to provide vacancies aimed at people with disabilities, but that these vacancies are not filled. Ten people with disabilities were also focused on as an important part of the research. In this way, both the business side and the disabled side were heard. The result of the research showed that there are unfilled vacancies for disabled people whose cause is the lack of knowledge of the Legislation on the part of PWD (people with disabilities). On the companies' side, they offer vacancies, but as disabled people lose benefits when they fill the vacancies, they do not accept.